ANALISIS KESEDIAAN MEMBAYAR IURAN KEBERSIHAN TERHADAP KEPUASAN MASYARAKAT DI LINGKUNGAN KELURAHAN LABUH BARU BARAT - Telly Handayani; Nursiah Chalid; Rita Yani Iyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this research to determine the willingness to pay and the factors that affect willingness to pay in Kelurahan Labuhbaru Barat. The sample used in this research is 98 KK. Data analysis method used in this research is descriptive. In this research the population is around the Kelurahan Labuhbaru Barat which amounts to 4746 KK. The sampling technique used was accidental.From the research conducted in the know that value of willingness to pay in Kelurahan Labuhbaru Barat is different. With the lowest WTP Rp 5000 and highest WTP Rp 30000. Total willingness to pay for the public to environmental hygiene is of 63.521.285,72. And the average value of the public’s willingness to pay per month in Kelurahan Labuhbaru Barat of 13384 per KK.Income variable(X1) effect on WTP(Y), while education variable(X2) and weight of household waste variable (X3) does not affect the WTP. This indication give the sence that determines the value of the magnitude of WTP (Y) in Kelurahan Labuhbaru Barat is income.Keywords : willingness to pay, Income, Education, Weight of household waste